Affron® a novel saffron extract (Crocus sativus L.) improves mood in healthy adults over 4 weeks in a double-blind, parallel, randomized, placebo-controlled clinical trial. (August 2017) - Kell, Graham; Rao, Amanda; Beccaria, Gavin; Clayton, Paul; Inarejos-García, Antonio Manuel; Prodanov, Marin
Highlights: affron ®, a natural extract from saffron (Crocus Sativus L.) improves mood without side effects after one month of treatment. Tension, depression, confusion and fatigue (POMS) diminished in the 28 mg/day treated group. The increased vigor (POMS) at a 28 mg/day dose. The 28 mg/day treated group showed a decrease in stress and depression (DASS-21). Abstract: Background: In recent years phytotherapy has been explored as a source for alternative treatments for mood disorders. One potential candidate is saffron ( Crocus sativus L.), whose main bioactive components are crocins and safranal. Objectives: The aim of this study was to investigate the efficacy of affron ®, a standardised stigmas extract from Crocus sativus L. for improving mood, stress, anxiety and sleep quality in healthy adults. Methods: In this 3 arm study, 128 participants self-reporting low mood but not diagnosed with depression, were given affron ® at 28 mg/day, 22 mg/day, or a placebo treatment in a randomized, double-blind, placebo-controlled trial for 4 weeks. Mood was measured at baseline and at the end of the study, using the POMS (primary outcome measure) and PANAS questionnaires, and the DASS-21 scale. Sleep was monitored using Sleep Quality Index (PSQI). Results: Analysis indicated a significant decrease in negative mood and symptoms related to stress and anxiety at a 28 mg/day dose (with a significant difference between 28 mg/day and placebo on the POMS Total Mood Disturbance scale, p  < 0.001, d  = −1.10), but no treatment effect at the 22 mg/day dose. Limitations: The main weaknesses of this investigation were found in the self-reporting nature of both the screening and the testing. Conclusions: affron ® increased mood, reduced anxiety and managed stress without side effects, offering a natural alternative to standard treatments.